Frequency and Characterization of Movement Disorders in Anti-IgLON5 Disease. (5th October 2021) - Gaig, Carles; Compta, Yaroslau; Heidbreder, Anna; Marti, Maria J.; Titulaer, Maarten J.; Crijnen, Yvette; Högl, Birgit; Lewerenz, Jan; Erro, María Elena; García-Moncó, Juan Carlos; Nigro, Pasquale; Tambasco, Nicola; et al.
Abstract : Background and Objectives: Anti-IgLON5 disease is a recently described neurologic disease that shares features of autoimmunity and neurodegeneration. Abnormal movements appear to be frequent and important but have not been characterized and are underreported. We describe the frequency and types of movement disorders in a series of consecutive patients with this disease. Methods: In this retrospective, observational study, the presence and phenomenology of movement disorders were assessed with a standardized clinical questionnaire. Available videos were centrally reviewed by 3 experts in movement disorders. Results: Seventy-two patients were included. In 41 (57%), the main reason for initial consultation was difficulty walking along with one or several concurrent movement disorders. At the time of anti-IgLON5 diagnosis, 63 (87%) patients had at least 1 movement disorder with a median of 3 per patient. The most frequent abnormal movements were gait and balance disturbances (52 patients [72%]), chorea (24 [33%]), bradykinesia (20 [28%]), dystonia (19 [26%]), abnormal body postures or rigidity (18 [25%]), and tremor (15 [21%]). Other hyperkinetic movements (myoclonus, akathisia, myorhythmia, myokymia, or abdominal dyskinesias) occurred in 26 (36%) patients. The craniofacial region was one of the most frequently affected by multiple concurrent movement disorders (23 patients [32%]) including dystonia (13), myorhythmia (6), chorea (4), or myokymia (4). Considering any body region, the most frequent combination of multiple movement disorders consisted of gait instability or ataxia associated with craniofacial dyskinesias or generalized chorea observed in 31 (43%) patients. In addition to abnormal movements, 87% of patients had sleep alterations, 74% bulbar dysfunction, and 53% cognitive impairment. Fifty-five (76%) patients were treated with immunotherapy, resulting in important and sustained improvement of the movement disorders in only 7 (13%) cases. Discussion: Movement disorders are a frequent and leading cause of initial neurologic consultation in patients with anti-IgLON5 disease. Although multiple types of abnormal movements can occur, the most prevalent are disorders of gait, generalized chorea, and dystonia and other dyskinesias that frequently affect craniofacial muscles. Overall, anti-IgLON5 disease should be considered in patients with multiple movement disorders, particularly if they occur in association with sleep alterations, bulbar dysfunction, or cognitive impairment.